2013
DOI: 10.3389/fnhum.2013.00581
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation in Optokinetic Stimulation Sensitivity between Omission and Substitution Reading Errors in Neglect Dyslexia

Abstract: Although omission and substitution errors in neglect dyslexia (ND) patients have always been considered as different manifestations of the same acquired reading disorder, recently, we proposed a new dual mechanism model. While omissions are related to the exploratory disorder which characterizes unilateral spatial neglect (USN), substitutions are due to a perceptual integration mechanism. A consequence of this hypothesis is that specific training for omission-type ND patients would aim at restoring the oculo-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Previous studies have shown that specific neglect dyslexia reading patterns predict the success of a targeted intervention. For example, Daini et al (2013) found that optokinetic stimulation only affected omission errors, and only in one out of two patients. Such observations may serve as the starting point for larger case studies with the ultimate goal to identify individualized and targeted interventions for specific impairments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that specific neglect dyslexia reading patterns predict the success of a targeted intervention. For example, Daini et al (2013) found that optokinetic stimulation only affected omission errors, and only in one out of two patients. Such observations may serve as the starting point for larger case studies with the ultimate goal to identify individualized and targeted interventions for specific impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous intervention studies targeted neglect defined as deficit of spatial attention and exploration (Kerkhoff & Schenk, 2012), but did not specifically measure improvements in single-word reading (see Daini et al, 2013;and Reinhart, Schindler, & Kerkhoff, 2011; for an exception using optokinetic stimulation). However, several studies used reading measures to evaluate the effect of different interventions on neglect symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in previous studies, sensory and cognitive therapies may have a differential impact on different neglect symptoms. 13,23 Gossmann et al 6 combined prism adaptation with a motor task. The patients improved on a test measuring egocentric symptoms, whereas there was no effect on allocentric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that omission errors were pathognomonic of ND. For Daini et al [8], omissions might be related to an exploratory deficit, and substitutions to a deficit of perceptual integration. Omissions at the level of the word [8] or the text [9] are specifically reduced by optokinetic stimulation, which improves oculomotor behaviour.…”
Section: Single Word Readingmentioning
confidence: 98%
“…For Daini et al [8], omissions might be related to an exploratory deficit, and substitutions to a deficit of perceptual integration. Omissions at the level of the word [8] or the text [9] are specifically reduced by optokinetic stimulation, which improves oculomotor behaviour. However, Primativo et al [10] showed that neglect errors in reading are identical when words are tachistoscopically presented, preventing saccades, or in an unlimited presentation duration, allowing saccades.…”
Section: Single Word Readingmentioning
confidence: 98%